2014
DOI: 10.1145/2700433
|View full text |Cite
|
Sign up to set email alerts
|

Haptic 3D Surface Representation of Table-Based Data for People With Visual Impairments

Abstract: The UN Convention on the Rights of Persons with Disabilities Article 24 states that "States Parties shall ensure inclusive education at all levels of education and life long learning." This article focuses on the inclusion of people with visual impairments in learning processes including complex table-based data. Gaining insight into and understanding of complex data is a highly demanding task for people with visual impairments. Especially in the case of table-based data, the classic approaches of braille-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The rest of the publications involved teachers participating in professional development and other participants across various contexts (e.g., visually impaired adults, Braier et al, 2014; medical patients, Wake et al, 2019). Our review also revealed a growing interest in using 3DP technology for students with special needs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rest of the publications involved teachers participating in professional development and other participants across various contexts (e.g., visually impaired adults, Braier et al, 2014; medical patients, Wake et al, 2019). Our review also revealed a growing interest in using 3DP technology for students with special needs.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies explored how to engage participants without visual impairments in designing 3D printed objects for individuals with visual impairments (Giraud et al, 2017; Kostakis et al, 2015; Pantazis & Priavolou, 2017; Stangl, Hsu, & Yeh, 2015; Stangl, Jernigan, & Yeh, 2015). In addition, two studies examined the educational uses of 3DP for students with special needs (Braier et al, 2014; Buehler et al, 2015). Overall, these findings suggest that 3DP learning is not limited to a particular age group, academic level, or type of educational setting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last years, VIs' assistive tools which use 3D and/or haptic technology have been developed [Kim and Yeh 2015, Braier et al 2015, Reusser et al 2019. Although the questionnaires represent a part of the scenario investigated, some intrinsic indications of why these technologies were not mentioned are the high cost of acquire them (and, consequently, use them) and the knowledge's lack about their existence.…”
Section: Challengesmentioning
confidence: 99%
“…Much of this involves the creation of tactile graphics which can be useful for students with a range of visual abilities [11]. Recent work in this space has explored using Lego bricks [4], 3D printed images [2,18,25] and toy robots [9] to represent course materials. This work focusses on auxiliary content, which must be accompanied by an in-person or recorded lecture, rather than creating accessible versions of original lectures, as we do here.…”
Section: Access To Lecture Contentmentioning
confidence: 99%